KONDISI SOSIAL EKONOMI MASYARAKAT NELAYAN PESISIR PANTAI AIR BANGIS, KECAMATAN SUNGAI BEREMAS, KABUPATEN PASAMAN BARAT - Aprimatul ilfa Aprimatul Ilfa; Khairani khairani (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
This study aims to: 1).To determine the income level of the Air Bangis Coastal fishing community 2).To determine the level of education of the Air Bangis Coastal Coastal fishing community 3).To determine the kinship relationship of the Air Bangis Coastal Coastal fishing community. This type of research is classified as quantitative descriptive. The data collection technique was carried out by means of observation, interviews and questionnaires. The sample in this study was 40 fishing trawlers. The analysis technique used in this research is descriptive, the formula used is the percentage formula and the Likert scale. The results of this study based on the objectives of the research conducted showed that 1). The social condition of the fishing community shows that the age of fishermen is dominated by productive age with good health. Work experience 16-20 years (38%). The level of education taken by fishermen is low with an average education of SD/MI (50%). The status of the house they occupy is their own (75%) and the ownership of the land occupied is rent (87%). 2). The main livelihood as fishermen with moderate income, namely Rp. 1,500,000 to Rp. 2,500,000.00 (50%) with 3 - 4 people (48%). Where kinship relations are classified as those created there are classified as good. The relationship between husband and wife is good (53%), father and children are classified as good (60%), kinship relations between the fishermen community are classified as good (75%). Keywords: Socio-Economic Conditions, Fishermen